Amphibians in a changing world: a global look at their conservation status - Loyola, Rafael (2015)
Currently, more than 40% of extant amphibian species are threatened with extinction and a quarter of them still lack information to be classified as threatened, being therefore enlisted as Data Deficient by the International Union for the Conservation of Nature (IUCN) (1,2). Furthermore, amphibians are the greatest underrepresented group in the global network of protected areas (PAs) worldwide. A decade ago, some studies showed that around 17% of amphibian species lived completely outside of protected areas (3). Obviously, the underrepresentation of amphibians in protected areas is much higher for range-restricted species that inhabit highly humanmodified landscapes. Even in face of this worrying scenario, since 2004 not a single update has been published showing amphibian species represented inside PAs at the global scale. Actually, there is a large gap of information, especially if we consider that today data on the distribution of many amphibian species are available, and the areas covered by PAs has increased over the last ten years from 11% to more than 13% worldwide